Javanese Tafsir Epistemology: Tracing the Source of Bisri Mustofa’s Thought in Al-Ibrīz li Ma’rifat Al-Qur’ān al-’Azīz Commentary - Habibillah, Putri Ghoida' (Institut Agama Islam Negeri (IAIN) Keiri, 2024)
This qualitative research attempts to trace the epistemology used by KH. Bisri Mustofa in compiling tafsir Al-Ibrīz li Ma'rifat Al-Qur'ān al-'Azīz. This is important to fulfill the need to validate information sources in an era of disinformation-prone disruption. This study, classified as a literature model, uses descriptive analysis based on Ibn Khaldun’s epistemological theory. For this reason, the primary source used is the book of Tafsir Al-Ibrīz li Ma’rifat Al-Qur'ān al-'Azīz in the pegon version, not latin as is widely circulated today. Secondary sources are also added in the form of books, articles, and other writings that are considered relevant to the topic of this study to support the study. The sources were collected using documentation techniques that were analyzed using Ibn Khaldun’s epistemological theory. From the operation of the study, it was found that Al-Ibrīz uses comprehensive sources in ratios, mu’tabar books, expert opinions, the Qur’an, hadith, and even isrāiliyyāt narration. From these sources, Ibn Khaldun’s statement regarding epistemological theory shows that Al-Ibrīz can be categorized as a compatible interpretation. However, it should be noted that not all sources of interpretation used by Bisri Mustofa are free from pros and cons related to their validity. This study shows that the integration of classical Islamic traditions with local Nusantara approaches in tafsir, such as Al-Ibrīz, produces inclusive and relevant works along with the changing times.